2019
DOI: 10.1002/ange.201906630
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Desorption Triggered by Circularly Polarized Light

Abstract: The interest in enantioseparation and enantiopurification of chiral molecules has been drastically increasing over the past decades,since these are important steps in various disciplines such as pharmaceutical industry,asymmetric catalysis,a nd chiral sensing.B ye xposing racemic samples of BINOL (1,1'-bi-2-naphthol) coated onto achiral glass substrates to circularly polarized light, we unambiguously demonstrate that by controlling the handedness of circularly polarized light, preferential desorption of enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Our earlier study showed that the emergence of optical activity from the racemate is temporally confined to the first 10 min of desorption. 16 After that, the measured g-value does not significantly change any more. This observation is reconfirmed by Figure 6B.…”
Section: Influence Of the Sample Morphology On The Generated Opticamentioning
confidence: 94%
See 4 more Smart Citations
“…Our earlier study showed that the emergence of optical activity from the racemate is temporally confined to the first 10 min of desorption. 16 After that, the measured g-value does not significantly change any more. This observation is reconfirmed by Figure 6B.…”
Section: Influence Of the Sample Morphology On The Generated Opticamentioning
confidence: 94%
“…The experimental setup is very similar to the one reported previously. 16 Herein, we present the key information for convenience of the reader and in addition, we highlight the specific steps that have been taken for the work presented in this contribution. The setup depicted in Figure 1 is based on an amplified Ti-sapphire laser system (CPA-2001, Clark-MXR Inc.), which provides 150-fs pulses with a central wavelength of 775 nm at a repetition rate of 1 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations